Water supply availability in island communities case of Island Garden City of Samal - Chavez, Rey C.
This study entitled"Water Supply Availability in Island Communities: Case of Island Garden City of Samal," was undertaken to determine the extent of the water provisions that cater to the demand of the different units in the urban, rural -urban, and rural areas of the Island Garden City of Samal (IGACOS) and recommend the courses of action that could improve the reliability and adequacy of some of these water provisions. To achieve this general objective, the study ascertained the extent of the water provisions in the urban, rural-urban, and rural areas of the island community, and determined how different units cope with their daily demand with the types of water provisions in the urban, rural-urban, and rural areas of the island community. The study also determined whether the income of the household units affects their responses to changes in their source of water provisions, particularly drinking water. Finally, the study determined the recommended courses of action that could improve the reliability and adequacy of some of the water provisions in the urban , rural-urban, and rural areas of the IGACOS. Considering there are 46 barangays in the IGACOS, the study made use of a two-stage sampling design and structured interview, with the aid of a prepared survey questionnaires for the different units, to generate information on the water provisions and how different units cope with their daily demand given the water provisions in the island community. The questionnaire for household units was also used to collect data on whether the income of the household units affects their responses to changes in their source of water provisions, particularly drinking water. The study made use of the Chi-Square Test of Independence to determine whether the two variables are related or independent of each other. The study found a range of water provisions in the island community such as the usual water supply provisions of rainwater collectors, shallow wells, springs, communal faucet systems, barangay water supply system, and those provided by the Island Garden City of Samal Water District (IGACOSWD) which are used for drinking, washing dishes and clothes, hygiene and sanitation, watering plants, among others. However, during changes in weather when water quality is affected or when it is not drinkable at all, an average of 67.68% and 49.44% of the household units and commercial units, respectively, obtained their drinking water from supplementary source, Fifty-two households and 105 households in Babak and Penaplata, respectively, regularly used drinking water bought from local vendors. Two commercial units in the rural-urban area of Caliclic consistently obtained their drinking water from "Dumoy" water sources in Davao City. Nonetheless, an average of 30.18% and 36.76% of the household units and commercial units respectively, still relied on the usual water provisions mentioned above.There were only two industrial units (furniture and cabinet manufacturing) covered in the study. These were in Penaplata where they got their drinking water from supplementary sources when water from the barangay water system is not safe for drinking. The study determined that the household's income could affect its choice of where to obtain their drinking water. Finally, the study determined there were economic implications of poor water quality to the people of the island community. Households paid a higher price to obtain drinking water from vendors in IGACOS and Davao City. Doing business along the designated coastal tourism areas is quite costly and could be a deterrent in stimulating further its burgeoning economic activities.
Keywords: Water supply -- Island Garden City of Samal